2015
DOI: 10.1007/s13277-015-3043-9
|View full text |Cite
|
Sign up to set email alerts
|

Silencing clusterin gene transcription on effects of multidrug resistance reversing of human hepatoma HepG2/ADM cells

Abstract: Abnormal clusterin (CLU) expression is associated with multidrug resistance (MDR) of hepatocellular carcinoma (HCC). In the present study, the CLU expression was analyzed in human hepatoma cells and chemoresistant counterpart HepG2/ADM cells. Compared with L02 cells, the overexpression of cellular CLU was identified in HepG2, HepG2/ADM, SMMC7721, Hep3B ,and PLC cells and relatively lower expression in Bel-7404, SNU-739, and MHCC97H cells. Specific short hairpin RNAs (shRNAs) to silence CLU gene transcription w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…It has been proven that OGX‐011 improves the efficacy of chemotherapy by downregulating the expression of clusterin and promoting apoptosis in several preclinical and clinical studies . Several studies have demonstrated that clusterin confers resistance to anticancer agents in HCC, including sorafenib (unpublished data), doxorubicin, gemcitabine and oxaliplatin …”
Section: Biological Functions Of Hsps In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that OGX‐011 improves the efficacy of chemotherapy by downregulating the expression of clusterin and promoting apoptosis in several preclinical and clinical studies . Several studies have demonstrated that clusterin confers resistance to anticancer agents in HCC, including sorafenib (unpublished data), doxorubicin, gemcitabine and oxaliplatin …”
Section: Biological Functions Of Hsps In Hccmentioning
confidence: 99%
“…Thus, siRNA or antisense oligodeoxynucleotide is used to knockdown the expression of clusterin. Silencing the expression of clusterin using siRNA obviously improves the efficacy of gemcitabine, oxaliplatin and doxorubicin in HCC treatment.…”
Section: Targeting Hsps In Hccmentioning
confidence: 99%
“…It encodes two isoforms with paradoxical activities: nuclear clusterin (nCLU) and secretory clusterin (sCLU), and wide distribution in tissues and body fluids with various biological functions including lipid transport, senescence, complements cascade, membrane recycling, cell adhesion, and programmed cell death [5][6][7]. The nCLU is localized in nucleus and considered to participate in cell death; on the contrary, the sCLU is mainly distributed in cytoplasm and always plays a cellprotective role with anti-apoptosis activity [8], and its abnormality has been determined in a wide variety of tumors with development and progression by contributing to angiogenesis, chemo-resistance, cell survival, or metastasis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The well recognized mechanism of classical MDR is the significant overexpression of human MDR1 gene encoding MDR1/P-glycoprotein (P-gp) that acts as an efflux pump on cell surface [8,9] . Intracellular anti-cancer drugs increasingly flow from cells through the efflux pump, thus drug concentrations become lower and cancer cells become resistant to chemotherapeutic drugs such as doxorubicin [10,11] . Recently, some studies have found diverse anticancer effects of metformin in the cells of lung, gastric, endometrial, breast, and other types of cancer [12,13] .…”
Section: Introductionmentioning
confidence: 99%